Development of High-Power Pulsed Fibre Laser Using Master Oscillator Power Amplifier (MOPA) System - Leong, Nathaniel Jenn Kwang (2020)
Mode-locked lasers are lasers with ultrashort pulses, typically in the range of a few femtoseconds. The mode-locked laser has many applications such as z-scan to determine non-linear index of a material and micromachining of transparent material. However, conventional solid state mode-locked lasers are large and expensive and require a complicated cooling system. A mode-locked fibre laser is inexpensive and is less bulky. However, they are not able to produce high output power that is comparable to the conventional solid state mode-locked laser. Therefore, to obtain high power, amplification is required. In this research, a mode-locked fibre laser using graphene oxide (GO) as saturable absorber will be developed. The mode-locked pulses will then be amplified using a two-stage amplification process to obtain higher output power. Due to non-linear effects in the fibre, the pulse will be significantly broadened due to supercontinuum generation which will be minimised by adding a length of single mode fibre (SMF) to broaden the pulse before amplification to reduce the intensity and thus, reduce the non-linear effects. This system is able to produce output power up to 164 mW. Some recommendations to further increase the output power and improve the performance of the mode-locked fibre laser system are given in this report.